MAKNA TOLERANSI DAN MODERASI BERAGAMA DALAM FILM DOKUMENTER - Ihsannulhaq, Pangeran Arsyad; Marini (Universitas Muhammadiyah Kotabumi, 2023)
In religious life, everyone is free to choose and carry out worship based on their own beliefs and true beliefs without any intimidation from certain groups. This is also what is reflected in the people of Pekon Ambarawa Pringsewu Lampung who apply various concepts of moderation in their daily lives. There are many religions that live in harmony there, such as Islam, Christianity, Catholicism, Hinduism and Buddhism. Film is one of the propaganda media to convey messages in a contemporary way in society. Apart from being informative and entertaining, packaging da'wah messages through films is also an effective communication medium for the public. Likewise with the documentary film